Peningkatan Cognitive Engagement Siswa dalam Pembelajaran dengan Pendekatan POE (predict-observe-explain) dan Multimedia Interaktif yang Dikembangkan Sendiri: Improvement of Students’ Cognitive Engagement in Teaching and Learning Process using POE (Predict-Observe-Explain) approach and Self-Developed Interactive Multimedia - Ismi Hafsari Idris; Syamsurizal Syamsurizal; Damris Muhammad (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
Students’ cognitive engagement in teaching and learning process is an important factor for successful learning. Improvement of students’cognitive engagement was investigated through a teaching and learning process using POE (predict-observe-explain) approach and self-developed interactive media. The objective of this study is to improve students’ cognitive engagement in teaching and learning process at junior high school. The development of interactive multimedia uses Animate CC and Four D and its validation were explained. The self-developed interactive multimedia was used with POE approachin teaching and learning process at junior high school. This three steps predict-observe-explain approach is used and students higher order thinking and total participants showing higher order thinking characteritics were analysed. It was found that the self-developed interactive multimedia isto contribute to the students’ active cognitive engagement.